Analisis Literatur Tentang Penerapan Etika Kerja dalam Meningkatkan Kinerja Organisasi - Dahliana; Susana Indriyati Caturiani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study examines the implementation of work ethics to improve organizational performance through a literature review. In a dynamic business environment, work ethics serve as a fundamental basis for fostering a healthy and productive work culture. Previous studies indicate that work ethics contribute positively to performance improvement by building trust, commitment, and employee loyalty. The method used is a literature review, analyzing various relevant journals and publications. The analysis results show that consistent implementation of work ethics can enhance job satisfaction, reduce conflicts, and boost productivity. Supporting factors, such as management commitment and strong organizational culture, play a vital role in the successful implementation of work ethics. Conversely, a lack of commitment from leadership can be a significant obstacle. These findings are expected to provide practical guidance for organizations in implementing work ethics to achieve sustainable performance